Studies On The Activity Of Isoniazid Derivatives And Their Combinations With Other Anti-TB Drugs On Mycobacterium Tuberculosis - Parumasivam, Thaigarajan (2012)

(untitled)
The low permeability of the cell envelope against hydrophilic anti-tuberculosis (TB) drugs especially isoniazid (INH), is one of the crucial factors that contribute to the intrinsic resistance in Mycobacterium tuberculosis. Previous studies have floated the idea that the anti-mycobacterial activity of INH can be enhanced by augmenting the hydrophilic INH into a hydrophobic/lipophilic compound. Therefore, a series of 13 derivatives with different hydrophobicity were synthesized by adding different hydrophobic acyl chain to the parent compound, INH.